Application of Legume Inoculum (Legin) to The Root Nodules and Peanut (Arachis hypogaea L.) Production on Peat Soil West Kalimantan - Anna Rizkia; Riza Linda; Zulfa Zakiah (Jurnal Biologi Tropis, 2022)
Peanuts (Arachis hypogaea L.) are food crops that have high economic value because of their nutritional content. One of the factors that affect the low production of peanuts in West Kalimantan is the condition of the soil dominated by peat soil causing soil fertility to be low. Application of Rhizobium or legin is expected to increase the production of peanuts (Arachis hypogaea L.). The purpose of the research was to find out the effect of legin application against the amount of root nodules and the production of peanut plants. The research was conducted from November 2020 to February 2021. This research used a Completely Randomized Design (CRD) consisting of 5 treatments namely control, application of legin 4 g/kg seed, 8 g/kg seed, 12 g/kg seed and 16 g/kg seed. The results showed application of legin has a real influence on the total weight of root nodules, the total number of root nodules, the number of effective root nodules, the number of filling pods, the number of seeds and the weight of seeds, but had no noticeable effect on the time of flowering. Legin application of 12 grams / kg of seeds is the best concentration to increase the production of peanuts grown in west Kalimantan peat soil, because it gives the best results to the number of pods content 11.33 pods, the number of seeds 24.16 seeds and the seed weight 19.73 grams.